Jakim językiem mówią politycy? Analiza poziomu czytelności exposé z wykorzystaniem Jasnopisu - Domagała, Mateusz (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*74.66px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.938179);" role="presentation">Exposé <span dir="ltr" style="left: calc(var(--scale-factor)*104.29px); top: calc(var(--scale-factor)*118.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991226);" role="presentation">is one of the most important political texts in Poland. The program speech con<span dir="ltr" style="left: calc(var(--scale-factor)*75.21px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.997288);" role="presentation">tains key information <span dir="ltr" style="left: calc(var(--scale-factor)*162.54px); top: calc(var(--scale-factor)*132.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978349);" role="presentation">regarding the plans of the new government for the term of office. <span dir="ltr" style="left: calc(var(--scale-factor)*74.72px); top: calc(var(--scale-factor)*146.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00868);" role="presentation">With the development of political marketing and the role of the media in Poland, the <span dir="ltr" style="left: calc(var(--scale-factor)*74.97px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.925819);" role="presentation">exposé <span dir="ltr" style="left: calc(var(--scale-factor)*103.28px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0078);" role="presentation">has become a <span dir="ltr" style="left: calc(var(--scale-factor)*160.19px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01379);" role="presentation">form of communication <span dir="ltr" style="left: calc(var(--scale-factor)*259.10px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01121);" role="presentation">not only as a <span dir="ltr" style="left: calc(var(--scale-factor)*313.12px); top: calc(var(--scale-factor)*160.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00066);" role="presentation">message of programming, <span dir="ltr" style="left: calc(var(--scale-factor)*75.22px); top: calc(var(--scale-factor)*174.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02188);" role="presentation">but also of image. The purpose of this article is to <span dir="ltr" style="left: calc(var(--scale-factor)*281.08px); top: calc(var(--scale-factor)*174.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02224);" role="presentation">study the changes in the readabil<span dir="ltr" style="left: calc(var(--scale-factor)*75.18px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.974432);" role="presentation">ity <span dir="ltr" style="left: calc(var(--scale-factor)*88.41px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02477);" role="presentation">of the program speech in the 1989–2019 period. It is now possible thanks to <span dir="ltr" style="left: calc(var(--scale-factor)*402.71px); top: calc(var(--scale-factor)*188.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03191);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*74.53px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.948038);" role="presentation">Jasnopis <span dir="ltr" style="left: calc(var(--scale-factor)*108.70px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.985473);" role="presentation">tool developed by <span dir="ltr" style="left: calc(var(--scale-factor)*181.36px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978396);" role="presentation">Włodzimierz Gruszczyński’s <span dir="ltr" style="left: calc(var(--scale-factor)*296.71px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.977547);" role="presentation">team. It uses the experience of <span dir="ltr" style="left: calc(var(--scale-factor)*74.40px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.995327);" role="presentation">American and Polish researchers regarding the analysis of the level of text readability, <span dir="ltr" style="left: calc(var(--scale-factor)*75.18px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01692);" role="presentation">including the formulas developed by <span dir="ltr" style="left: calc(var(--scale-factor)*227.32px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02894);" role="presentation">Robert Gunning and Walery Pisarek. The evo<span dir="ltr" style="left: calc(var(--scale-factor)*75.17px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02742);" role="presentation">lution <span dir="ltr" style="left: calc(var(--scale-factor)*101.49px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990412);" role="presentation">of the <span dir="ltr" style="left: calc(var(--scale-factor)*126.66px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.925819);" role="presentation">exposé<span dir="ltr" style="left: calc(var(--scale-factor)*152.37px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.995194);" role="presentation">, and above all the process of simplifying program speech, has not <span dir="ltr" style="left: calc(var(--scale-factor)*74.91px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00617);" role="presentation">yet been described in the literature. This article is an attempt to <span dir="ltr" style="left: calc(var(--scale-factor)*331.07px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00712);" role="presentation">describe the research <span dir="ltr" style="left: calc(var(--scale-factor)*75.25px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.05239);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*87.58px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991089);" role="presentation">the readability <span dir="ltr" style="left: calc(var(--scale-factor)*146.37px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.968267);" role="presentation">of the text and to <span dir="ltr" style="left: calc(var(--scale-factor)*213.80px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00131);" role="presentation">indicate <span dir="ltr" style="left: calc(var(--scale-factor)*247.32px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.982285);" role="presentation">the changes in the <span dir="ltr" style="left: calc(var(--scale-factor)*319.79px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.924403);" role="presentation">exposé <span dir="ltr" style="left: calc(var(--scale-factor)*347.27px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.995472);" role="presentation">and their reasons.